Cost‐effectiveness of sofosbuvir for the treatment of chronic hepatitis C‐infected patients. Issue 11 (7th April 2015) - Cure, S.; Guerra, I.; Dusheiko, G.
Summary The efficacy of treatment for hepatitis C genotype 1 infection has significantly improved with the introduction of first‐generation protease inhibitors. However, there remains a need for effective treatments for patients infected with other genotypes, for nonresponders and patients unsuitable for interferon. Sofosbuvir is the first nucleotide polymerase inhibitor with pan‐genotypic activity. Sofosbuvir‐based regimens have resulted in >90% sustained virological response across treatment‐naïve genotype 1–6 patients in five phase III clinical trials of sofosbuvir administered with ribavirin or pegylated interferon and ribavirin. This analysis evaluates the cost‐effectiveness of sofosbuvir within the current licensed indication, for genotype 1–6 in the UK. A Markov model followed a cohort of 10 000 patients over lifetime, with approximately 20% initiating treatment for compensated cirrhosis. Sofosbuvir‐regimens were compared to telaprevir, boceprevir, pegylated interferon and ribavirin, or no treatment. Costs and outcomes were discounted at 3.5%. The cost perspective utilized costs applicable to the National Health Service in the UK. Sofosbuvir proved to be cost‐effective in most patient populations with incremental cost‐effectiveness ratios (ICERs) at £11 836/QALY and £7292/QALY against telaprevir and boceprevir, respectively. In genotype 3, sofosbuvir had a weighted ICER of £18 761/QALY. Sofosbuvir‐based regimens are a cost‐effective option for the majority of hepatitis C‐infected patients in the United Kingdom although the incremental cost‐effectiveness varies by genotype and regimen. Sofosbuvir and ribavirin is an alternative regimen for patients unsuitable for interferon.